Immature argasid ticks: diagnosis and keys for Neotropical region - Barros-Battesti,Darci Moraes (2013)
Many argasid tick species are known only through their larval descriptions, in which the chaetotaxy, together with other external morphological characteristics, has been used to separate genera and species. However, the illustrations of these features are based on optical microscopy alone and many of these features are not clearly defined. Because of the difficulties in determining the larval and nymph stages of some genera, we have prepared illustrated keys for the immature stages of argasids, including an up-to-date list of the known species of the Neotropical region. We have also included an illustrated key for larvae of the Ornithodoros species from Brazil, based on scanning electron microscopy.